2017
DOI: 10.1155/2017/5435831
|View full text |Cite
|
Sign up to set email alerts
|

Extraoral Taste Receptor Discovery: New Light on Ayurvedic Pharmacology

Abstract: More and more research studies are revealing unexpectedly important roles of taste for health and pathogenesis of various diseases. Only recently it has been shown that taste receptors have many extraoral locations (e.g., stomach, intestines, liver, pancreas, respiratory system, heart, brain, kidney, urinary bladder, pancreas, adipose tissue, testis, and ovary), being part of a large diffuse chemosensory system. The functional implications of these taste receptors widely dispersed in various organs or tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 358 publications
(346 reference statements)
1
40
1
2
Order By: Relevance
“…TAS2Rs have been discovered in various non‐taste cell types, including cardiac myocytes, gut enteroendocrine cells, leukocytes, sperm and upper airway epithelial cells 27,30,31 . We have provided evidence to show that TAS2R14 is functionally expressed in human epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…TAS2Rs have been discovered in various non‐taste cell types, including cardiac myocytes, gut enteroendocrine cells, leukocytes, sperm and upper airway epithelial cells 27,30,31 . We have provided evidence to show that TAS2R14 is functionally expressed in human epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown that extraoral taste receptors mediate various physiological processes including immune responses of the upper airway, nutrient uptake in the gut, and testis development 27,30,31,38 . Wölfle et al showed that keratinocytes upregulated differentiation genes in the presence of bitter tastants and hypothesized that TAS2R signaling in these cells promotes differentiation and epidermal barrier formation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we need to pay attention to the side effects of bitter tastants for drugs since many bitter tastants are toxins. In fact, the extra-oral expression of TAS2Rs has been hypothesized to cause off-target effects of bitter medications (Clark et al, 2012; Gilca and Dragos, 2017). Therefore, the suitable dose will be critical for developing drugs based on bitter tastants.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…6 These are unique concepts in Ayurveda which can potentially be applied to all living things that are a source of food and medicine in this world. 7 CP is described as being pungent (katu) and bitter (tikta) in taste, piercing in quality (teekshna), hot in potency (ushnaveerya), pungent post-digestion (katuvipaka), with special effect of boosting the intellect (medhya). It improves cognition, memory, digestion, relieves constipation, aids wound healing and is also prescribed for anemia like conditions, liver disorders, certain skin diseases and arthritis.…”
Section: Ayurvedamentioning
confidence: 99%